Stress-Testing of liquidity risk in TARGET2 - Patrick Papsdorf; Luca Arciero; Juan Carlos Frutos de Andres; Matti Hellqvist; Patrick Heyvaert; Alexandros Kaliontzoglou; Ronald König; Kasperi Korpinen; Clement Martin; Alexander Müller; Miguel Perez Garcia de Mirasierra; Maxime Ponsart; et al. (European Central Bank (ECB), 2017)
The paper reports the outcome of the stress-testing of liquidity risk in the TARGET2 payment system, with the study having been conducted by an ad-hoc group composed of operators and overseers of TARGET2. The study aims to assess the resilience of the system, defined as the network of its participants, and the appropriateness of liquidity levels under tightened liquidity conditions. The scenarios analysed are based on extreme shocks to the value of collateral of different levels and types that lead to a decrease in the intraday credit lines available in TARGET2 and, as a result, the payment capacity of TARGET2 participants. The tool used to perform these stress tests is the TARGET2 simulator, which provides access to real transaction level data and allows simulations to be run by changing parameters, in this case the credit lines. The period under analysis is one maintenance period for the years 2008 to 2013. In general, the stress-testing indicates that the system is resilient under the stress scenarios; liquidity levels seem to be appropriate and supported by the efficient liquidity management features of TARGET2. Even in the worst simulated event of a 70% drop in all collateral value, 80-90% of TARGET2 turnover would have been settled. The scenario results take also into account that the period under analysis was characterised by unconventional monetary policy measures.
Keywords: C63; E42; E58; G01; 330; TARGET2; stress testing; simulation; liquidity risk; principles for FMIs